Analysis of Centrifugal Pump Machine Performance Using the Overall Equipment Effectiveness (OEE) Method (Case Study: PT. XYZ) - Gatot Basuki HM; Alesandro Sheva Mifthada (Journal of Applied Sciences, Management and Engineering Technology, 2023)
Improving performance in a company is a key factor in increasing efficiency and productivity. However, often the improvement efforts made are ineffective because they do not address the root cause of the problem. The Total Productive Maintenance (TPM) concept with its components can clearly identify the root cause of the problem and its contributing factors, allowing improvements to be focused on the appropriate aspects. One method of measuring machine performance used is Overall Equipment Effectiveness (OEE), which calculates factors such as availability, performance efficiency, and quality level. In a case study at PT.XYZ, OEE was used to analyze the performance of distribution pump machines. During the period of August 2022, the OEE value for each pump machine reached 99%, which exceeded the world-class OEE of 85%. However, the analysis showed that Idling Minor Stop Losses was the main cause of losses that affected machine effectiveness, with a percentage of losses reaching 82%.